(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers military issues in the work of Olzhas Suleimenov. O. Suleimenov knew about the war not by hearsay, he was friends with Rakhimzhan Koshkarbayev, Dmitry Snegin and Baurzhan Momyshuly and heard about the war another truth ... It is no coincidence that the author often regrets about the fact that so far the Kazakh literature does not present a novel about that war, filled with truth. The author, in describing the events of the war years, starts from the formula: «the war touched everyone» trying to understand a person caught up in the border situation, faced with a choice between life and death, and sets out what is happening in the ballad form which is characterized by tense tragic dynamics inherent in such subjects. His poems about the war are concrete, filled with factographic information; between the lines, in the subtext there emerges what the poet did not express in the poetic form. The article analyzes such verses of Olzhas Suleimenov as: «Their names rustle as assault flags», «Nameless height», dedicated to the memory of Kurban Badelbaev and others